ZEB1 Expression Is Correlated With Tumor Metastasis and Reduced Prognosis of Breast Carcinoma in Asian Patients. (3rd July 2015) - Xiang, Shuai; Liu, Ya-Min; Chen, Xu; Wang, Ya-Wen; Ma, Ran-Ran; Wu, Xiao-Juan; Gao, Peng
ABSTRACT Tumor metastasis is one of the key events leading to tumor relapse and poor prognosis. Nowadays, increasing evidences demonstrated that ZEB1 was implicated in human carcinogenesis. However, involvement of ZEB1 deregulation in tumorigenesis in Asian patients with breast carcinoma remains elusive. The present study included 102 Asian patients with breast carcinoma treated by surgery from January of 2005 to December of 2006, and the expression of ZEB1 was evaluated by immunohistochemistry. To further assess the prognostic value of ZEB1, Kaplan–Meier curves were constructed. In this study, elevated levels of ZEB1 expression was found in carcinomas with higher aggressive potential. We also correlated expression of ZEB1 with lymph node metastasis (P = 0.021), advanced clinical stage (P = 0.012) in all cases, and high tumor grade (P = 0.047) in invasive ductal carcinoma. Furthermore, our data suggested an elevated level of Ki-67 expression in cases with positive expression of ZEB1. Clinically, reduced overall survival and disease-free survival were observed in cases with positive ZEB1 expression than that in negative cases. Our results correlated ZEB1 with aggressive potentials of breast carcinoma and revealed a possibility for ZEB1 as a prognostic marker in breast carcinoma.